Does COVID-19 Pandemic Affect Bank Credit Risk? A Panel Data Analysis - Ririn Riani (SMART Insight, 2021)
This study aims to examine the impact of the COVID-19 pandemic on banking credit risk in Indonesia, namely conventional banks and Islamic banks which are proxied through NPL and NPF variables. This study used a sample of 12 conventional commercial banks and 12 Islamic commercial banks in Indonesia. The data used is quarterly data, namely from the 1st quarter of 2017 to the 4th quarter of 2020. Furthermore, in this paper, dummy variables are used to describe the period before and after the COVID-19 pandemic that caused various declines in the economy. The method in this study uses a panel data analysis approach. The results show that COVID-19 significantly affects credit risk in the overall model and conventional bank models. Meanwhile, no correlation was found between the COVID-19 pandemic and the Islamic bank model. Furthermore, the variables found to have a significant relationship with credit risk are bank capital, total loans, and bank profitability.